In vitro performance of a shape memory polymer foam-coated coil embolization device. (November 2017) - Boyle, Anthony J.; Wierzbicki, Mark A.; Herting, Scott; Weems, Andrew C.; Nathan, Adam; Hwang, Wonjun; Maitland, Duncan J.
Highlights: Design of an implantable medical device utilizing shape memory polymer foam Benchtop demonstration of device performance for treatment of intracranial saccular aneurysms. Preliminary analysis of device biocompatibility by pilot verification studies. Abstract: Intracranial saccular aneurysm treatment using endovascular embolization devices are limited by aneurysm recurrence that can lead to aneurysm rupture. A shape memory polymer (SMP) foam-coated coil (FCC) embolization device was designed to increase packing density and improve tissue healing compared to current commercial devices. FCC devices were fabricated and tested using in vitro models to assess feasibility for clinical treatment of intracranial saccular aneurysms. FCC devices demonstrated smooth delivery through tortuous pathways similar to control devices as well as greater than 10 min working time for clinical repositioning during deployment. Furthermore, the devices passed pilot verification tests for particulates, chemical leachables, and cytocompatibility. Finally, devices were successfully implanted in an in vitro saccular aneurysm model with large packing density. Though improvements and future studies evaluating device stiffness were identified as a necessity, the FCC device demonstrates effective delivery and packing performance that provides great promise for clinical application of the device in treatment of intracranial saccular aneurysms.